The Effect of Managerial Ownership on Firm Value with Accounting Conservatism and Earnings Quality as Intervening Variables - Diah Safitri; Windu Mulyasari; Nana Nofianti (Review of Accounting and Taxation, 2023)
Purpose - This research aims to determine the effect of managerial ownership on firm value with accounting conservatism and earnings quality as intervening variables. Design/methodology/approach - Multiple linear regression with SPSSv25 software and route analysis with an online Sobel calculator were utilized for analysis. Finding - According to the findings of this study, management ownership has a negative and considerable impact on firm value. Furthermore, managerial ownership has a considerable and favorable impact on accounting conservatism and earnings quality. Accounting conservatism and profit quality can thus be employed as intervening factors in this investigation. Originality - This research raises the issue of firm value seen from the perspective of ownership structure. The difference of this research is investigating the influence of these factors by looking at accounting conservatism and earning quality. The research was conducted because the influence of ownership structure on firm value gave inconsistent results.